Spatial simulation of job location mobility of highly qualified employees in Mainfranken - Seynstahl, Christian; Rauh, Jürgen (ERDKUNDE, 2015)
Affected by changing frame conditions of gainful occupation, employees are facing a growing need to be geographically mobile on the labour market. Although the knowledge intensification of the overall economy is progressing, the demand for high-skilled human capital is regionally selective. This paper deals with the inner German job location mobility of academics and occupationally highly qualified employees, who had been working in Mainfranken between 1999 and 2008. In a first step, the job location mobility for both types of highly skilled employees will be explored by analysing their labour market biographies. In a second step, those findings will be used to develop a modelling approach, which simulates the supra-region mobility of Mainfranken’s highly qualified employees on an individual level. The model is a two-step approach using age group-specific mobility rates to determine how many highly qualified employees changed their job location in a twelve-month period. Next, and based on the utility theory, allocation and matching processes for academics are simulated in a Monte Carlo simulation. Simulation outputs will be presented through the example of academics.